Metabolic effects of a prolonged, very-high-dose dietary fructose challenge in healthy subjects. Issue 2 (4th December 2019) - Smajis, Sabina; Gajdošík, Martin; Pfleger, Lorenz; Traussnigg, Stefan; Kienbacher, Christian; Halilbasic, Emina; Ranzenberger-Haider, Tamara; Stangl, Anna; Beiglböck, Hannes; Wolf, Peter; Lamp, Tanja; Hofer, Astrid; et al.
ABSTRACT: Background: Increased fructose intake has been associated with metabolic consequences such as impaired hepatic lipid metabolism and development of nonalcoholic fatty liver disease (NAFLD). Objectives: The aim of this study was to investigate the role of fructose in glucose and lipid metabolism in the liver, heart, skeletal muscle, and adipose tissue. Methods: Ten healthy subjects (age: 28 ± 19 y; BMI: 22.2 ± 0.7 kg/m 2 ) underwent comprehensive metabolic phenotyping prior to and 8 wk following a high-fructose diet (150 g daily). Eleven patients with NAFLD (age: 39.4 ± 3.95 y; BMI: 28.4 ± 1.25) were characterized as "positive controls." Insulin sensitivity was analyzed by a 2-step hyperinsulinemic euglycemic clamp, and postprandial interorgan crosstalk of lipid and glucose metabolism was evaluated, by determining postprandial hepatic and intra-myocellular lipid and glycogen accumulation, employing magnetic resonance spectroscopy (MRS) at 7 T. Myocardial lipid content and myocardial function were assessed by 1 H MRS imaging and MRI at 3 T. Results: High fructose intake resulted in lower intake of other dietary sugars and did not increase total daily energy intake. Ectopic lipid deposition and postprandial glycogen storage in the liver and skeletal muscle were not altered. Postprandial changes in hepatic lipids were measured [Δhepatocellular lipid (HCL)_healthy_baseline: −15.9 ± 10.7 compared with ± ΔHCL_healthy_follow-up: −6.9 ± 4.6; P = 0.17] and hepatic glycogen (Δglycogen_baseline: 64.4 ± 14.1 compared with Δglycogen_follow-up: 51.1 ± 9.8; P = 0.42). Myocardial function and myocardial mass remained stable. As expected, impaired hepatic glycogen storage and increased ectopic lipid storage in the liver and skeletal muscle were observed in insulin-resistant patients with NAFLD. Conclusions: Ingestion of a high dose of fructose for 8 wk was not associated with relevant metabolic consequences in the presence of a stable energy intake, slightly lower body weight, and potentially incomplete absorption of the orally administered fructose load. This indicated that young, metabolically healthy subjects can at least temporarily compensate for increased fructose intake. This trial was registered at www.clinicaltrials.gov as NCT02075164.